Associations Between Vancomycin Exposure and Acute Kidney Injury Within the Recommended Area Under the Curve Therapeutic Exposure Range Among Patients With Methicillin-Resistant Staphylococcus aureus Bloodstream Infections. (22nd January 2022) - Lodise, Thomas P; Scheetz, Marc; Carreno, Joseph J; Chambers, Henry; Fowler, Vance; Holland, Thomas L
Abstract: Among patients with methicillin-resistant Staphylococcus aureus bacteremia, vancomycin-associated acute kidney injury increased as a function of the day 2 area under the curve (AUC), even for daily AUCs within the recommended therapeutic range (400–600). Further data are needed to determine if daily AUCs <400 can be maintained without compromising efficacy.